Psychoanalytic, Psychosocial, and Human Rights Perspectives on Enforced Disappearance - Giovanna Bianchi, Maria; Luci, Monica (Taylor & Francis, 2024)
Disappearance, Luci, Torture, Enforced, Bianchi, Human, Psychoanalysis, Trauma, enforced, disappearance, psychoanalytic theory, disappearance, human